Radioiodination of andrographolide and its biodistribution in mice for inflammatory tracer - Jutti Levita; Cahya Nova A.; As’ari Nawawi; Slamet Ibrahim (Indonesian Journal of Pharmacy, 2010)
Andrographolide,  a  bioactive  component  of  Andrographis  paniculata (Burm.F)  Nees,  is  the  major  lactone  diterpenoidal  bicyclic  constituent  in  this plant  which  has  proven  to  exert  anti-inflammatory  activity  in  vitro  which  was occurred via  several mechanism, e.g inhibition of inducible nitric oxide synthase (iNOS),  inhibition  of  radical  oxygen  species,  and  inhibition  of  NF-kappaB activation. The labeling with radionuclide is often used for therapy, detection and quantification of metabolites in the body. Even though the metabolites are very low  in  concentration  they  can  be  detected  by  the  energy  they  emitted. Radionuclide  can  be  used as  radiotracer  to  detect  whether  drug  really interacts with  its  target.  The  objective  of  this  research  is  to  synthesize 131I-labelled andrographolide  and  to  study  its  biodistribution  in  mice  to  understand  the location  of  its  organ  target.  Indirect  radioiodination  of  andrographolide  wascarried  out  by  using  bromine  as  the  leaving  group  and  followed  by  fast iodination  at  40oC,  yielded  72.6  %  purity  of  the  labeled  compound.  Iodination was occurred through proton substitution at C-12. Then the andrographolide-131I was  injected  into  lateral  vein  of  mice’s  tail  to  study  its  biodistribution.  The compound  was  distributed  in  all organs  with the  highest  accumulation  occurred in  the  stomach  (16.87  %/gram  organ).  The  result  showed  that  inducing  the animals  with  LPS  caused  inflammation  in  the  stomach  and  increased  the production  of  prostaglandin  as  proven  by  the  distribution  of  the  radioligand  in that organ.Key words: andrographolide, radioiodination, anti-inflammatory, biodistribution